Two new quill mite species (Prostigmata: Syringophilidae) parasitizing Australian birds - Glowska, Eliza; Laniecka, Izabella (Zootaxa, 2013)
Two new quill mite species (Prostigmata: Cheyletoidea: Syringophilidae), Syringophilopsis philemonis sp. nov. from Phi-lemon citreogularis (Gould) (Passeriformes: Meliphagidae) and Megasyringophilus cacatua sp. nov. from Cacatua gal-erita (Latham) (Psittaciformes: Psittacidae) are described from Australia.